Economic impact of climate change on Malaysian rubber production - Borkotoky, Parthajyoti (2012)
The incidence and intensity of extreme weather will be more frequent, which will likely challenge human and natural systems more than normal change. Agricultural sector falls under the primary damage sector due to climate change and is considered one of the most vulnerable sector to climate change. Climate has been changing in the conventional rubber growing regions of the country and the current temperature is at the higher end of the optimal temperature range for rubber crop. Thus further increases will adversely affected growth and productivity of natural rubber. The main objective of this study is to estimate the economic impact of climate change on natural rubber in Peninsular Malaysia and to capture the marginal impact of weather conditions on the viability of production systems along with the future climate change impact by predicting the economic impact due to the expected climate change. The present study uses and extends the Ricardian Model to estimate the climate change impacts on Malaysian rubber production using time series data from 1980 -2010. Impacts were estimated by changes in net revenue of rubber for estates and smallholders and combination of both with change in climate. The future impact of change in temperature that is increase in temperature was found to have nonlinear effects on natural rubber production. The results of this study also highlight the importance of precipitation for natural rubber. Marginal impacts of the precipitation and temperature indicate direct and negative relationship between rubber net revenue. The results were in line to what was expected. Furthermore marginal increase of temperature and precipitating will results in a loss of about RM 208 million in total. Based on future climate change scenarios from Atmosphere/Ocean General Circulation Model (AOGCMs) the rubber industry will bear a loss between RM 239/Ha to RM 805/Ha if no action is taken and in broader scale it losses between RM 246 million to RM 829 million in total.